New techniques for infection and recovery of schistosomes from animals - Agrawal, M C (The Indian Journal of Animal Sciences, 2012)
Two new techniques have been described-one for infecting the guineapigs with schistosome cercariae and the other forrecovery of blood-flukes from them with the advantage of their possible use in other animal species. For infecting theguineapigs, counted number of freshly Shed cercariae of Schistosoma incognitum and S. spindale were taken in twoseparate small (7 cm x 15 cm) transparent LDPE polythelene bags which enveloped the hind paws (tail in other animals)of the guinea-pig and held above the ground to avoid splitting of the bags.In the perfusion technique automatic pipetting machine has been replaced by a vertical water pump commonly usedin the desert coolers. After severing the hepatic portal vein, a 16 gauze hypodermic needle (its size regulated saline flow).till liver turned through a PVC tube with the pump was inserted in the left ventricle of the guineapig and pump was startedtill liver turned pale. The perfusate was filtered through a black cotton cloth which was transferred into a petri-dish tocollect the blood nukes.